The Realities of Witchcraft and Popular Magic in Early Modern Europe - Bever, E. author. aut Link
XXII, 627 p.
Keywords: Exploring the elements of reality in early modern witchcraft and popular magic, through a combination of detailed archival research and broad-ranging interdisciplinary analyses, this book complements and challenges existing scholarship, and offers unique insights into this murky aspect of early modern history.